2015
DOI: 10.1002/hast.452
|View full text |Cite
|
Sign up to set email alerts
|

When Should Genome Researchers Disclose Misattributed Pahentage?

Abstract: As analytic tools for genomic sequencing improve, biomedical research will increasingly use this method to draw inferences based on comparisons between the genetic data of a set of individuals thought to be related to each other. Cases in which genomic sequencing will be very useful include those in which a child has a rare or undiagnosed disease that might have an underlying genetic etiology. Researchers will be able to sequence the pediatric proband and both parents to compare their genomes in hopes of findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Second, what happens to this information when the patient reaches maturity? Although there is some guidance around disclosures of incidental discovery of misattributed paternity, such as during genetic testing, 19,20 there has been little discussion about whether and how to document paternity information when shared by a parent with the expectation of confidentiality. Documentation of paternity in this case is necessary because treatment recommendations may potentially be modified as a result of this new information.…”
Section: Documentation Of Sensitive Information Disclosed By a Parentmentioning
confidence: 99%
“…Second, what happens to this information when the patient reaches maturity? Although there is some guidance around disclosures of incidental discovery of misattributed paternity, such as during genetic testing, 19,20 there has been little discussion about whether and how to document paternity information when shared by a parent with the expectation of confidentiality. Documentation of paternity in this case is necessary because treatment recommendations may potentially be modified as a result of this new information.…”
Section: Documentation Of Sensitive Information Disclosed By a Parentmentioning
confidence: 99%
“…In response to some of these concerns, some researchers have advocated for universal nondisclosure (Mandava, Millum, & Berkman, 2015; Palmor & Fiester, 2014). Several case studies that considered the familial and social ramifications of disclosure concluded that the risks of revealing misattributed paternity outweighed the costs of withholding that information (Adlan & Have, 2012; Avci, 2017).…”
Section: Designing Field-based Paternity Studiesmentioning
confidence: 99%
“…This argument seems more convincing in a research context and indeed, the consensus has generally been that the discovery of misattributed parentage ought not to be disclosed in a research setting where it is not relevant to the research question. Mandava et al argue that “ nondisclosure should be the default position for researchers ” 14. In clinical practice, the issue has not previously arisen routinely because the use of parental testing to interpret a child’s result was rare until the advent of genomic medicine.…”
Section: Disclosure Optionsmentioning
confidence: 99%